Influence of phosphorus‐grafted expandable graphite on the flame‐retardant property of UHMWPE composite. (4th November 2018) - Wang, Huaming; Cao, Jingshi; Cao, Changlin; Guo, Yiyou; Luo, Fubin; Qian, Qingrong; Huang, Baoquan; Xiao, Liren; Chen, Qinghua
Abstract : In this paper, an efficient flame retardant, 9, 10‐dihydro‐9‐oxa‐10‐phosphaphenanthrene‐10‐oxide (DOPO) was covalently grafted onto the surface of expandable graphite (EG). The resultant DOPO‐grafted expandable graphite (EG‐g‐DOPO) was characterized by Fourier transform infrared spectroscopy, energy dispersive spectroscopy, and X‐ray photoelectron spectroscopy (XPS), respectively. The thermal stability of EG‐g‐DOPO was also evaluated by thermogravimetric analysis (TGA). Moreover, a series of flame‐retardant ultra‐high‐molecular‐weight polyethylene (UHMWPE) composites with various concentrations of EG‐g‐DOPO were prepared and evaluated. The results show that the UHMWPE composite with 20 wt% EG‐g‐DOPO possesses a satisfactory UL‐94 flame‐retardant grade (V‐0) and a high limiting oxygen index (30.6%). The residual char of the UHMWPE composite with higher EG‐g‐DOPO concentration shows more compact and integrated, providing an efficient barrier for heat release.